Therapeutic Workshops of Imagination - Santos Bispo, Fábio; Gusmão Pimentel, Sabrina (Guará Journal, 2019)
This article proposes a theoretical reflection based on the report of the Therapeutic Imagination Workshops, part of an interproject of the Extension Program "Each Two with Their Mania" (CDSM), the Therapeutic Workshops for Adolescents, at the Federal University of Espírito Santo (UFES). These workshops aim to offer the community an important service in child and adolescent mental health treatment. The collective space of the therapeutic workshops is an important mental health tool, as it can be used to process anxiety and other forms of psychological distress. Role-playing games (RPGs) are used as a therapeutic resource, in which participants create their characters to express their needs. The idea is that the game functions as a symbolic support for working through the impasses of adolescence. A decrease in patients’ psychological distress and the conflicts expected at this stage of life have been observed. Over the past eighteen months, 182 sessions have been conducted in these workshops. Extension workers gain valuable experience throughout their training by monitoring the therapeutic process from patient intake through psychological examination and development of the therapeutic plan in interdisciplinary team meetings.